Study of the antibacterial activity of Inula viscosa L. leaf extracts on some types of intestinal bacteria in poultry. - حسين , حسن; توفيق دلّا,; فهيم عبد العزيز , (Latakia University Journal -Biological Sciences Series, 2024)
The research aims to demonstrate the effect of tarium plant extracts on the bacteria that cause hemorrhagic intestinal infections in poultry. This study was carried out in the microbiology laboratory at the Faculty of Agricultural Engineering at Tishreen University and the drug and microbiology laboratory at the Faculty of Pharmacy at Tartous University, where the leaves of the tartan plant were collected from the Safita region in The months of October and November of 2021, after which the leaves were dried and preserved until use. Susceptibility tests were conducted for the three studied bacteria using the previous four extracts, and the study showed that E. coli, S. aureus, and C. Perfringes bacteria were sensitive to the four extracts used, with the exception of E. coli bacteria, which showed resistance to the ethanolic extract, chloroform, and dichloromethane when The two concentrations were 20 and 40 microliters without the appearance of any inhibition halo, while the ethyl acetate extract gave an inhibitory effect on the bacteria used at the three added concentrations. The highest diameter of the inhibition ring was at the concentration of 80 microliters, where the average diameter of the inhibition ring reached (18.11, 25.52, and 23.14 mm). ), respectively, compared to the control DMSO 5%, the diameter of the inhibition ring reached 6 mm for E. coli, 6.6 for S. aureus, and 6.3 for C. perfringes. Also, the bacteria Streptococcus aureus and Clostridium Perfringes did not show any resistance to the extracts used and at the three concentrations applied, and they gave the highest average diameter of the bacterial growth inhibition ring at a concentration of 80 microliters for the ethyl acetate extract (25.52 and 23.14 mm) and methanol (33.55 and 30.74 mm). Chloroform (27.91 and 26.18 mm) and dichloromethane (25.93 and 24.64 mm), respectively, compared with the control (5% DMSO), in which the average diameter of inhibition was 6.6 mm for Streptococcus aureus and 6.3 mm for Clostridium perfringes. The results indicate that the extracts of the leaves of the plant have antimicrobial activity against the pathogenic bacterial species used, and thus they could be a source of natural antibiotics in the future.